2023
DOI: 10.3390/plants12233974
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Wheat Gluten Content and Processing Quality: An Analysis of Drip Irrigation Nitrogen Frequency

Tianjia Hao,
Rong Chen,
Jing Jia
et al.

Abstract: Drip irrigation is a water-saving and fertilizer-saving application technology used in recent years, with which the frequency of drip irrigation nitrogen application has not yet been determined. In order to investigate the effects of different drip irrigation nitrogen application frequencies on the processing quality of medium-gluten wheat (Jimai22) and strong-gluten wheat (Jimai20 and Shiluan02-1), a two-year field experiment was carried out. Two frequencies of water and N application were set under the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Mor et al [159] reported that the sedimentation index was 3% higher when the N rate was split into five rather than two portions. In a study by Hao et al [156], the sedimentation index was 5% higher when the total N rate of 210 kg ha −1 was applied in four rather than two splits.…”
Section: Protein Complex Quality and Enzyme Activity In Grainmentioning
confidence: 92%
See 1 more Smart Citation
“…Mor et al [159] reported that the sedimentation index was 3% higher when the N rate was split into five rather than two portions. In a study by Hao et al [156], the sedimentation index was 5% higher when the total N rate of 210 kg ha −1 was applied in four rather than two splits.…”
Section: Protein Complex Quality and Enzyme Activity In Grainmentioning
confidence: 92%
“…In the work of Zhong et al [155], grain hardness peaked in response to 60 kg N ha −1 applied in BBCH stage 17 or 31, and it was 8% lower when N fertilizer was applied in BBCH stage 37. Hao et al [156] found that grain hardness was reduced by around 10% when the total N rate of 210 kg ha −1 was split into two portions (applied at the beginning of stem elongation and during flowering) than when the same N rate was split into four portions (beginning of stem elongation, heading, flowering, and grain filling). In turn, Blandino et al [157] reported that the hardness of wheat grain was not affected when the total N rate of 130 kg ha −1 was applied in one split (BBCH stage 23) or in two splits (BBCH stages 23 and 32).…”
Section: Milling Qualitymentioning
confidence: 99%